Panhypopituitarism as a Presenting Manifestation of Neurosarcoidosis – A Rare Case Report (Journal of Dhaka Medical College, 2025)
Sarcoidosis is a multisystem disease characterized by non-caseating granuloma that affects the nervous system occasionally. When neurosarcoidosis infiltrate the pituitary gland leading to panhypopituitarism, result can be devastating. We present here a case of 30-year-old lady who presented with fever and headache for 6 months along with prolonged period of amenorrhea and forgetfulness. She also had increased thirst and polyuria. Her hormone profiles were suggestive of panhypopituitarism. MRI of brain showed a contrast enhancing lesion in the sellar and suprasellar region along with nodular leptomeningeal enhancement . We retrogradely searched for the underlying reason behin`d this .Her MT was 0 along with ground glass opacity in both lung fields in HRCT chest which made the diagnosis of neurosarcoidosis most likely. We treated her with prednisolone to manage neurosarcoidosis and secondary adrenal insufficiency along with sequential hormone replacement with desmopressin and levothyroxine . Follow up MRI of brain done 3 months later showed near complete resolution of lesion along with significant clinical improvement.J Dhaka Med Coll. 2024; 33(2) : 80-86